Biology of the flotilla worm Metaponpneumata rogenhoferi Moschler (Lepidoptera: Noctuidea) - ALVAREZ-R., ALONSO (Revista Colombiana de Entomología, 1986)
In the North of Tolima, the flotilla worm Metaponpneumata rogenhoferi Moschler (Lepidoptera: Noctuidae), has been an endemic cotton pest since 1960; its morphology and biology have not been studied. A study was conducted to obtain basic information on this species, at the Entomology Laboratory of "Nataima" Regional Center of the Colombian Agricultural Institute (ICA) at Espinal, Tolima. The Center has an altitude of 420 m.a.s.l., an average temperature of 30 ± 2°C, and relative humidity between 60 and 70%. Individual observation of larval development permited to verify that M. rogenhoferi has polychromatic juvenile forms, such as green, pink, and almost black larvae. At 30 ± 2°C, the mean duration in days of the egg and pupal stages was 2.0 and 9.8, respectively. Larvae passed through five instars; the mean duration in days of each was: 2.1, 2.0, 1.8, 1.7, and 3,9, respectively. The total duration in days, from egg to adult, was 23.4. A 24°/o of the pupae entered diapause, with a duration between 27 and 85 days.